Image‐based management of empiric lung stereotactic body radiotherapy (SBRT) without biopsy: Predictors from a 10‐year single institution experience. Issue 6 (26th April 2018) - Hasan, Shaakir; Colonias, Athanasios; Mickus, Timothy; VanDeusen, Matthew; Wegner, Rodney E.
Abstract : Background: There is emerging reliance on clinical imaging for the diagnosis, prognosis, and treatment evaluation of early stage non‐small cell lung cancer (NSCLC) in patients deemed too high risk for biopsy. We report our experience of clinically diagnosed NSCLC treated empirically with stereotactic body radiotherapy (SBRT) to validate the imaging parameters used for management in this high‐risk population. Methods: We reviewed 101 empiric lung SBRT cases and profiled imaging specifics of computed tomography and positron emission tomography for diagnosis and follow‐up. Secondarily, we identified potential correlates of disease progression with Cox regression multivariate analysis. Results: Fifty‐seven men and 43 women aged 45–94 (median 76) were treated with a median dose of 48 Gy in four fractions. The median nodule diameter was 1.6 cm (0.6–4.5 cm) and most were spiculated ( n  = 58), right‐sided ( n  = 63), and in the upper lobe ( n  = 68). Median follow‐up and survival rates were 14 and 28 months, respectively. Local control at three years was 94%. Freedom from any progression at one and three years was 85% and 69%, respectively. Toxicity ≥ grade 3 included two grade 3 dyspneas. A pre‐treatment standard uptake value > 4.1 was the only significant predictor of disease progression. Conclusion: This study illustrates the instrumental role of modern clinical imaging for the effective management of presumed early stage NSCLC treated with empiric lung SBRT. As lung SBRT without tissue confirmation becomes more common, hopefully these assertions can be prospectively validated.